Fibrous feeds in the Mediterranean area: Characterization and utilization - Bruni R.; Antongiovanni M. (Exploitation of Mediterranean roughage and by-products, 1998)
A brief description and a classification of the most important fibrous feeds of the Mediterranean area are presented. The major limiting factors to their utilization as animal feeds are then discussed: the main constraint is the poor nutritive value because of the very low digestibility as a consequence of the quality of the structural carbohydrate fractions. After the introduction of the methodological approach adopted to evaluate the nutritive potential of the studied feeds, the amounts produced and the possible beneficial effect of the socio-economic aspect of animal farming from the improvement of the nutritive value are finally discussed.